Improved Social Studies Learning Outcomes Through the Mind Map Method for Grade 5 SDN Ketitang - Ika Noormaningtyas (Universitas Sebelas Maret, 2020)
This research is motivated by the problem of low social studies learning outcomes for grade 5 students. This is because teachers often use the lecture method, students only listen and record all information from the teacher so they consider social studies material to be difficult. This study aims to determine whether there is an increase in learning outcomes for theme 7, especially the content of social studies lessons through mind maps in grade 5 SD Negeri Ketitang, Godong District, Grobogan Regency. The research was conducted in March-April 2020 in the 5th grade of SD Negeri Ketitang, Godong District, Grobogan Regency as the research subject. The results showed that the social studies learning outcomes in the initial conditions were only 38.1% of students who reached the KKM. There was an increase in the first cycle of learning outcomes to 57.14% of students and in the second cycle increased to 85.71% of students who reached the KKM. In learning, teachers and students should more often apply the Mind Map method so that students can develop their imagination and absorption power of the material being taught.